2000
DOI: 10.1172/jci10203
|View full text |Cite
|
Sign up to set email alerts
|

Caspases determine the vulnerability of oligodendrocytes in the ischemic brain

Abstract: Although oligodendrocytes (OLGs) are thought to be vulnerable to hypoxia and ischemia, little is known about the detailed mechanism by which these insults induce OLG death. From the clinical viewpoint, it is imperative to protect OLGs as well as neurons against ischemic injury (stroke), because they are the only myelin-forming cells of the central nervous system. Using the Cre/loxP system, we have established a transgenic mouse line that selectively expresses p35, a broad-spectrum caspase inhibitor, in OLGs. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
82
2

Year Published

2001
2001
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(88 citation statements)
references
References 49 publications
4
82
2
Order By: Relevance
“…34,35 The work described here provided further support for this hypothesis by demonstrating the critical role of caspase-11 in activating both caspase-3 and caspase-7 during LPS-induced shock. Furthermore, we established the temporal sequence of caspase-11, caspases-3/-7 and caspase-1 activation, and the independence of caspase-3 activation from that of cytokine secretion, at least in the early phase of LPS response.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…34,35 The work described here provided further support for this hypothesis by demonstrating the critical role of caspase-11 in activating both caspase-3 and caspase-7 during LPS-induced shock. Furthermore, we established the temporal sequence of caspase-11, caspases-3/-7 and caspase-1 activation, and the independence of caspase-3 activation from that of cytokine secretion, at least in the early phase of LPS response.…”
Section: Discussionsupporting
confidence: 64%
“…C. Specificity of YVAD in the inhibition of caspase-1 but not caspase-11. 35 S-labeled in vitro translated substrates (*IL-1b for caspase-1 and *PARP for caspase-11) were incubated with recombinant caspase-1 (Casp-1) or caspase-11 (Casp-11). Increasing concentrations of pan-caspase inhibitor zVAD.fmk (zVAD) and caspase-1 inhibitor acYVAD.cmk (YVAD) were added (2, 10 and 20 mM where indicated) in the cleavage assay to examine the specificity of the inhibitor, ac.YVAD.cmk.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it has been demonstrated that intracellular apoptotic signals leading to a common endpoint, i.e., caspase-3 activation, occur in both neurons and glia following spinal cord injury (Emery et al, 1998;Hayashi et al, 1998;Springer et al, 1999;Beattie et al, 2000;Citron et al, 2000;Springer et al, 2000). Similar studies have documented evidence of caspase-3 activation in other types of CNS injury models, including head trauma and ischemia/stroke (Gottron et al, 1997;Hara et al, 1997;Yakovlev et al, 1997;Endres et al, 1998;Ni et al, 1998;Posmantur et al, 1998;Velier et al, 1999;Zhang et al, 1999;Clark et al, 2000;Eldadah and Faden, 2000;Shibata et al, 2000;Zhu et al, 2000). Numerous in vitro studies have demonstrated that caspase-3 activation is initiated, in part, by upstream events that result in the release of cytochrome c and Smac/DIABLO from the mitochondria (Liu et al, 1996;Bossy-Wetzel et al, 1998;Skulachev, 1998;Yang and Cortopassi 1998;Slee et al, 1999;Du et al, 2000;Verhagen et al, 2000).…”
Section: The Caspase-3 Apoptotic Cascadementioning
confidence: 96%